Disparity in Judges' Decisions Regarding Divorce Due to Apostate Husbands (RechtJiva, 2025)
Divorce is often the culmination of conflict in a marriage, especially when religious differences are the main cause. In Indonesia, this is a sensitive and complex issue. Divorce due to religious differences in marriage is one of the complex problems often faced in the Religious Courts. One aspect that is interesting to study is divorce cases due to apostate husbands. This research explores two different court decisions in similar cases, one resulting in fasakh and the other in talak, using the perspective of the Shafi'i Madhhab. This study aims to analyze the judge's consideration in divorce cases due to apostate husbands from the perspective of the Shafi'i Madzhab in two court decisions: 121/Pdt.G/2021/PA.MII and 2349/Pdt.G/2021/PA.Wsb. The method used is normative juridical with a case approach, using primary, secondary, and tertiary legal sources as well as document studies in the form of court decisions and Islamic legal literature. The analysis is carried out by considering the legal views of the Shafi'i Madzhab. The findings reveal significant differences in judicial considerations despite the similarity of the cases. The 121/Pdt.G/2021/PA.MII decision ruled the marriage annulled through fasakh, in line with Shafi'i jurisprudence, which holds that apostasy automatically nullifies a marriage contract. Conversely, the 2349/Pdt.G/2021/PA.Wsb decision applied talak, focusing on positive law while overlooking the doctrinal stance of the Shafi'i school. The research offers guidelines for handling similar cases in the future in Religious Courts by applying the jurisprudential approach of the Shafi'i school in shaping legal decisions.